2018
DOI: 10.1108/ssmt-09-2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the vapour concentration decrease on the solder joints temperature in a vacuum vapour phase soldering system

Abstract: Purpose The vacuum vapour phase soldering method was investigated by numerical simulations. The purpose of this study was to examine the temperature changes of the solder joints during the vapour suctioning process. A low pressure is used to enhance the outgassing of the trapped gas within the solder joints, which otherwise could form voids. However, the system loses heat near the suction pipe during the suctioning process, and it can result in preliminary solidification of the solder joints before the gas cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…According to the industrial experiments if the difference in onset of melting is over 0.2 -0.3s, then the probability of component displacement failure increases considerably. The effect of the low pressure generation on the solidification of the solder joint were also examined during the vacuum VPS process (Illés et al, 2018B). It was found that process zone can suffers considerable heat loss on the suction pipe which results in the drop of the solder joints temperature.…”
Section: Numerical Simulation Of the Vps Processmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the industrial experiments if the difference in onset of melting is over 0.2 -0.3s, then the probability of component displacement failure increases considerably. The effect of the low pressure generation on the solidification of the solder joint were also examined during the vacuum VPS process (Illés et al, 2018B). It was found that process zone can suffers considerable heat loss on the suction pipe which results in the drop of the solder joints temperature.…”
Section: Numerical Simulation Of the Vps Processmentioning
confidence: 99%
“…It was found that process zone can suffers considerable heat loss on the suction pipe which results in the drop of the solder joints temperature. In the case of thin FR4 PCB (<1.5mm) with small components (<0.5mm), the solder joints can solidify during the low pressure generation before the voids would be removed from the solder joints (Illés et al, 2018B).…”
Section: Numerical Simulation Of the Vps Processmentioning
confidence: 99%
“…We use the knowledge that the transition temperature from the gaseous (saturated steam of boiling liquid) to the liquid state is precisely defined as the boiling point of liquid. The saturated vapour condenses and transfers its latent heat of vaporisation to the surface of assemblies (Illés et al, 2017;Illes et al, 2018). At the boiling point of liquid, the properties of the capacitor change from a single plate to a parallel plate capacitor, filled with two dielectric environments in a stacked configuration: condensed fluid and saturated vapour (air).…”
Section: Introductionmentioning
confidence: 99%
“…Reflow soldering technology is the most widespread technique for creating the electrical and mechanical connection between the electronics components and the printed circuit board in electronics mass manufacturing today as described by Illés et al (2018). The continuous request for electronic devices that are faster, smarter and smaller is the driving force in electronics technology, which resulted in the shrinkage of component sizes.…”
Section: Introductionmentioning
confidence: 99%